Evaluation of major coronary artery Bifurcation angles with digital angiography: A detailed study of prevalence in the Upper Euphrates Basin - Deniz, Gulnihal; Kavakli, Ahmet; Kucukukur, Murat; Kose, Evren; Karaca, Ilgin (Professional Medical Publications, 2022)
Objectives: To investigate the diversity and average values of bifurcation angles in a large population to help develop new methods. Methods: One thousand five individuals (504 females, 501 male) who visited the Cardiology Polyclinic of Firat University Hospital with the complaint of chest pain between 2010 and 2015 were evaluated retrospectively. Bifurcation angle measurements between LMCA-CX, CX-LAD, LMCA-LAD, CX-OM1, CX-OM2, LAD-D1, LAD-D2, RCA-RMD, RCA-RVD and PDA-PL were evaluated in all cases. Results: Bifurcation angles between LMCA-LAD, LMCA-Cx and LAD-Cx branches with > 90 wide angle bifurcations, and Cx-OM1, Cx-OM2, LAD-D1, LAD-D2, RCA-RMD and PDA-PL with <70 Y type bifurcation angle were found to be high in male and female individuals. The RCA-RVD in female individuals was <70 Y-type bifurcation in 14 (2.8%) people, > 70-90 T-type bifurcation in 209 (41.5%) people, and > 90 wide angle bifurcation in 281 (55.8%) people. Results for male subjects were compatible with this. The correlations of all angles were examined. Robust positive correlations (p <= 0.001) were found for the angular measurements between the main branches and the side branches (Cx-OM1, Cx-OM2, LAD-D1, LAD-D2 and RCA-RMD, PDA-PL). Conclusion: With the help of developing technology, we believe that all this coronary angiography data will guide bifurcation stent techniques, which are essential alternatives to bypass.
Keywords: Bifurcation; Bifurcation angles; Coronary artery; CX; LMCA; LAD; RCA; PDA; PL